ECONOMIC RELATIONS BETWEEN THE COUNTRIES OF CENTRAL ASIA (American Journal of Interdisciplinary Research and Development, 2024)
This article shows the current state and prospects of the economic cooperation between the Republic of Uzbekistan and the Republic of Kazakhstan, as well as the efforts made to develop bilateral trade and activate mutual cooperation. At the same time, several areas of economic cooperation, such as investments in the economy, major projects, transfer of goods and services, cooperation in the field of transport and logistics, business in the banking sector, etc., tax issues, intellectual property and other indicators are presented.